PERAN PENDIDIKAN DALAM PERUBAHAN SOSIAL DI SEKOLAH - Amanah Fatiha, Keysha Alea; Sari , Elya Komala; Dewi, Meyana (DE FACTO : Journal Of International Multidisciplinary Science, 2024)
Education is important for people's lives. Because with education a person is able to actualize himself. Education provides progress in human thinking, so that their standard of living increases. In its development over time, education has transformed into a system.. In other words, education is a process of developing abilities to influence students to be able to adapt as best as possible to their environment. Educational institutions (schools) are often considered to be one of the most conservative and static social institutions in society. Schools as formal educational institutions are less able to follow and respond to the rapid changes occurring in society. In order for educational activities to be able to equip students to face life challenges in the future, it is necessary to anticipate what life challenges will be in the future. Rapid changes in people's social life often give rise to phenomena in society and are related to the world of education. Because of this, there are those who accuse the world of education of failing to develop the morals of its students.